A case of chronic exocrine pancreatic insufficiency in a gastric bypass patient: Chronic pancreatic insufficiency in gastric bypass patient - Wagle, Laxman; Regmi, Dhiraj Raj; Regmi, Sabita (Journal of Surgery and Medicine, 2024)
Exocrine pancreatic insufficiency (EPI) is a significant complication of bariatric surgery, but its frequency and outcomes are not well-studied. If EPI is not diagnosed, it can result in nutritional deficiencies, dehydration, and acute kidney damage. Our patient, a 47-year-old woman, underwent Roux-en-Y gastric bypass (RYGB) surgery due to morbid obesity four years ago and lost contact with outpatient follow-ups. She came to us presenting chronic diarrhea and fatigue and was diagnosed with chronic pancreatic exocrine deficiency based on a low fecal elastase level. After starting her on pancreatic enzymes, her symptoms resolved. It is crucial to maintain a high degree of suspicion in order to diagnose EPI in patients who have undergone RYGB. The fecal elastase test, which is both reliable and inexpensive, is an effective diagnostic tool for EPI; prompt treatment can alleviate symptoms within days.